Analysis of deamidation artifacts induced by microwave-assisted tryptic digestion of a monoclonal antibody - Formolo, Trina; Heckert, Alan; Phinney, Karen W. (Analytical and bioanalytical chemistry, 2014)
The thorough characterization of biopharmaceuticals is essential for ensuring their quality and safety since many potential variations can cause changes to the properties of a drug that may be detrimental to the patient such as decreased efficacy, shorter half-life or increased immunogenicity. Prior to approval and release, protein-based drugs are subject to a battery of analyses to assess the nature of those parameters that are considered critical quality attributes. In some cases the analytical method used may itself cause modifications that are impossible to distinguish from those induced by the intended test conditions (e.g. storage time/temperature, light exposure) which are used to assess drug stability. It is therefore important to develop and utilize analytical methods which impose as few artifactual modifications as possible. Asparagine deamidation is a common protein modification and it is known to be induced during tryptic digestion. Therefore we examined common tryptic digestion protocols and compared their propensities towards asparagine modification. Since microwave assisted hydrolysis techniques are often used to shorten digestion times and the effect on deamidation is unknown we sought to compare this method against alternate digestion protocols.